Does Positional Advantage has Impact on School Performance ? Evidence From Middle Vocational School - Pajar Machmud (SAJMR : Southeast Asian Journal of Management and Research, 2024)
An organization can outperform competitors only if it can establish a strategic position, that is, a difference that can be maintained. This difference is defined as a positional advantage. In this study, positional advantage is defined as utilizing internal resources and organizational capabilities as a valuable source of competitive advantage to beat competitors and improve company performance. This study aims to examine the first-order positional advantage indicators and examine the effect of positional advantage on institutional performance in Vocational High Schools (SMK) in Indonesia. The analytical technique used in this research is partial least square (PLS-SEM). The population in this study was 358 SMK in West Java Province, Indonesia. The intended respondent is the Principal at the SMK. The results of this study reveal that there is a positive influence between positional advantage and institutional performance.